2014
DOI: 10.1093/nar/gku929
|View full text |Cite
|
Sign up to set email alerts
|

ETS1 is a genome-wide effector of RAS/ERK signaling in epithelial cells

Abstract: The RAS/ERK pathway is commonly activated in carcinomas and promotes oncogenesis by altering transcriptional programs. However, the array of cis-regulatory elements and trans-acting factors that mediate these transcriptional changes is still unclear. Our genome-wide analysis determined that a sequence consisting of neighboring ETS and AP-1 transcription factor binding sites is enriched near cell migration genes activated by RAS/ERK signaling in epithelial cells. In vivo screening of candidate ETS proteins reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 58 publications
6
99
2
Order By: Relevance
“…ETS1 has been shown to play an important role in the progression of breast cancer (46) and has been recently linked to the RAS/ERK pathway in carcinomas (47). Bonetti et al recently demonstrated that FLI1 and ETS1 cooperatively contribute to the growth of diffuse large B-cell lymphoma, and influence gene expression related to germinal center differentiation (48).…”
Section: Discussionmentioning
confidence: 99%
“…ETS1 has been shown to play an important role in the progression of breast cancer (46) and has been recently linked to the RAS/ERK pathway in carcinomas (47). Bonetti et al recently demonstrated that FLI1 and ETS1 cooperatively contribute to the growth of diffuse large B-cell lymphoma, and influence gene expression related to germinal center differentiation (48).…”
Section: Discussionmentioning
confidence: 99%
“…The GGAA repeat reporter was created by annealing complementary DNA oligonucleotides (See Supplemental Experimental Procedures) containing 7 tandem repeats of GGAA or GAGA and cloning into pGL4.25. Dual luciferase reporter assay (Promega) measured luciferase activity as described (Plotnik et al, 2014). Firefly luciferase values were normalized to renilla values.…”
Section: Methodsmentioning
confidence: 99%
“…These ETS proteins activated transcription of cell migration genes by binding cis-regulatory sequences that have neighboring ETS and AP-1 transcription factor binding sites. However, this ETS/AP-1 binding is not specific to ERG, ETV1, ETV4, and ETV5, because ETS1 can also bind ETS/AP-1 sequences and activate transcription of cell migration genes in KRAS-mutant cancer cells (Plotnik et al, 2014). Therefore the molecular mechanism behind the specific biological function of ERG, ETV1, ETV4, and ETV5 in prostate cells is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a method for identifying gene expression programs regulated by RAS/ERK signaling using RNA-sequencing ( RNA-seq ) and differential gene expression analysis [ 7 ]. Using a MEK inhibitor , we disrupt the constitutive activation of the RAS/ RAF/MEK/ERK pathway in the DU145 prostate cancer cell line and then isolate mRNA .…”
Section: Introductionmentioning
confidence: 99%
“…1 for an overview of the main protocol steps). Using this approach, we have identifi ed nearly 700 genes signifi cantly regulated by RAS/ERK signaling, enriched in genes involved in cell migration , invasion, and proliferation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%